LRRC4 Suppresses E-Cadherin-Dependent Collective Cell Invasion and Metastasis in Epithelial Ovarian Cancer - Zhao, Chunhua; She, Xiaoling; Zhang, Yan; Liu, Changhong; Li, Peiyao; Chen, Shuai; Sai, Buqing; Li, Yunchao; Feng, Jianbo; Liu, Jia; Sun, Yingnan; Xiao, Songshu; et al. (Frontiers in Oncology, 2020)
Epithelial ovarian cancer (EOC) is the most malignant gynaecologic carcinoma and is of a high incidence of death due to detection at late stages when metastasis already occurs. However, the mechanism underlying metastasis of EOC remains unclear. Analysis of the open database and experiments with immunochemistry showed that LRRC4 is lowly expressed in high-grade serous ovarian cancer (HGSC) cells and during EOC metastasis. The 3D cell culture system and the orthotopic ovarian xenograft model infected with LRRC4-containing adeno-associated virus serotype 9 (AAV9) were used to confirm collective invasion and metastasis of cells in vitro and in vivo. Phos-tag SDS-PAGE was used to detect the phosphorylation of LRRC4 and PIK3R1. A number of experiments with methods such as co-immunoprecipitation and immunoblotting were performed to explore the mechanism for the actions of LRRC4 and PIK3R1 in EOC metastasis. An inverse correlation between LRRC4 and E-cadherin expression was detected in the regions of invasion in primary EOC tissues and metastatic ascites. LRRC4 binds to the cSH2 domain of PIK3R1 and inhibits the activity of PIK3R1, without disrupting the physical interactions between PIK3R1 and PIK3CA. LRRC4 inhibits EOC metastasis by targeting E-cadherin-dependent collective cell invasion and does so by inhibiting the PIK3R1-mediated AKT/GSK3β/β-catenin signalling pathway. LRRC4 functions as a tumour suppressor gene to inhibit EOC collective invasion and metastasis in vitro and in vivo and does so by directly binding to the cSH2 domain of PIK3R1 to exert its regulatory function. Our findings provide a potential novel approach for metastasis prognosis and a new strategy for the treatment of EOC.